Bangkok Precipitated: Cloudbursts, Sentient Urbanity, and Emergent Atmospheres. Issue 2 (3rd April 2021) - Sangkhamanee, Jakkrit
Abstract: Bangkok often floods. This paper examines the effects of city deluge as a result of urban assemblage: complex, distributed and disjunctive relations between the city's amphibious ecologies and landscapes, its dilapidated drainage infrastructure, its varied transport systems, its weather patterns, and the movements of people. During cloudbursts, many of Bangkok's missing masses become plainly and frustratingly, visible. Using ethnographic description as a "material diagnostics, " I explore how irritated, perturbed, urban atmospheres emerge out of disjunctive infrastructural constellations. Cloudbursts make perceptible such atmospheres as forms of sentient urbanism, in which distributed sensations are generated by intersecting material itineraries moving across multiple assemblages. As affects and agitations move from street level to social media, rain precipitates matters of urgent, urban concern and critique.